A process-based model of methane consumption by upland soils - A F Sabrekov; M V Glagolev; P K Alekseychik; B A Smolentsev; I E Terentieva; L A Krivenok; S S Maksyutov (Environmental Research Letters, 2016)
This study combines a literature survey and field observation data in an ad initio attempt to construct a process-based model of methane sink in upland soils including both the biological and physical aspects of the process. Comparison is drawn between the predicted sink rates and chamber measurements in several forest and grassland sites in the southern part of West Siberia. CH _4 flux, total respiration, air and soil temperature, soil moisture, pH, organic content, bulk density and solid phase density were measured during a field campaign in summer 2014. Two datasets from literature were also used for model validation. The modeled sink rates were found to be in relatively good correspondence with the values obtained in the field. Introduction of the rhizospheric methanotrophy significantly improves the match between the model and the observations. The Q _10 values of methane sink observed in the field were 1.2–1.4, which is in good agreement with the experimental results from the other studies. Based on modeling results, we also conclude that soil oxygen concentration is not a limiting factor for methane sink in upland forest and grassland ecosystems.